Broadband Fixed Wireless Access A System Perspective - Engels, Marc; Petre, Frederik (Signals and Communication Technology, 2006)
Broadband Fixed Wireless Access provides a systematic overview of the emerging WiMax technology, and much of the material is based on the practical experiences of the authors in building broadband wireless systems. This material will be of significant interest to network architects and developers of broadband fixed wireless access products. With the adoption of the IEEE 802.16 standard and the advent of next generation equipment, the WiMax technology has been growing in interest. The authors discuss applications at microwave frequencies between 2 and 11 GHz that could be attractive options for operators without an existing access infrastructure for reaching end users with broadband services. This introductory volume demystifies the technology and provides technical exposure to the various system trade-offs. Additionally, the book features the following highlights: Detailed modeling of broadband fixed wireless access propagation channel, including new measurements for its time variation. An extensive overview of the IEEE 802.16 standard. A tutorial on implementation challenges for WiMAX terminals. Discussion of the suitability of various multi-antenna techniques. Elaboration of different techniques, i.e. autodirecting antennas, bridging with WLAN, and multi-hop networking, that can be used to reduce the cost of ownership of a WiMAX network for an operator. The authors cover a wide range of topics, from network deployment to implementation of terminals. Wireless professionals will gain a head start from the information on WiMAX technology. This is a must read book when starting with broadband fixed wireless access.